Identification of Pests and Diseases in Tomato Plants in Jeprono Village, Karangbangun District, Karanganyar Regency - Sihotang, Dini Rosita; Syafitri , Dewi; Octaviana, dhea Cindy; Septianingrum, Parigi Akhiri; Asy-Syfaiyyah, Asma’ (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The tomato (Solanum lycopersicum), is a very valuable horticultural plant that is extensively grown in Jepron Village, Karangbangun District, Karanganyar Regency. However, pests and diseases frequently limit tomato yield. Finding the kinds of pests and illnesses that target tomato plants in the region is the goal of this study. Direct field observation and laboratory identification are two components of the qualitative descriptive research methodology. The study's findings found a number of pests, including armyworms (Helicoverpa armigera), fruit flies (Bactrocera sp.), and earthworms (Phytothetora infestans). Furthermore, brown spots (Alternaria solani), root rot (Ralstonia solanacearum), and leaf rot (Phytophthora infestans) were discovered. In order to increase harvest yields, this study suggests using environmentally friendly farming technologies and implementing integrated pest management (IPM) strategies. It is anticipated that the findings of this study will serve as a guide for managing pests and diseases to enhance the well-being of nearby farmers.